3(1-8s)=-27

Simple and best practice solution for 3(1-8s)=-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(1-8s)=-27 equation:


Simplifying
3(1 + -8s) = -27
(1 * 3 + -8s * 3) = -27
(3 + -24s) = -27

Solving
3 + -24s = -27

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -24s = -27 + -3

Combine like terms: 3 + -3 = 0
0 + -24s = -27 + -3
-24s = -27 + -3

Combine like terms: -27 + -3 = -30
-24s = -30

Divide each side by '-24'.
s = 1.25

Simplifying
s = 1.25

See similar equations:

| 2(4x-2)=3x+6 | | -7(x+8)=-84 | | 159+x+9=12x+7 | | 8x+26=6(-2x-6)+2 | | N-13=-18 | | -3(1-7n)=-31-7n | | 25*(5)525-66=5 | | -6(6r+3)+5(r+5)=69 | | 5x+18=6x+14 | | x+132=125 | | 6(2+6k)-8=-176 | | -(b-5)=b-3 | | -3(-2+x)=-10 | | -11+a=-2(7a-2) | | 19r=-57 | | x^2+(1-i)x-i=0 | | -4v+2(-1-6v)=-130 | | -2(2y-6)-y=-2(y-3) | | 2a-4=3(a-4) | | x^2+(1-i)x-1=0 | | 2(2y-1)=-19 | | -32+8v=6(v-7) | | 2b^2+3b-2= | | -42=3(6+8b)+6(-3b-7) | | 9x-2=133 | | 60=-5(6n-6) | | 38-n=5+4(-2n+3) | | -26+6p=-8(1-3p) | | 2(r+4)=-35 | | 580=-20b | | 9y+12=84 | | 21x-3=40x |

Equations solver categories